Structure and phase composition of Nb/Ti system subjected to compression plasma flow impact - Shimanskii (Shymanski) V. I. Vitali Igorevich; Cherenda N. N. Nikolay Nikolaevich; Uglov V. V. Vladimir Vasilievich; Astashinski V. M. Valentin Mironovich; Kuzmitski A. M. Anton Mikhaylovich (2015, 2015)
Title screen